Formulation of multipurpose grease from titanium dioxide manufacturing waste (red gypsum) - Arumugam, Nithiya (2009)
This study describes the formulation of multipurpose grease using red gypsum from titanium dioxide manufacturing wastes. Greases produced with different amount of fume silica (FS) and red gypsum in its compositions. The effect of red gypsum’s and fumed silica’s concentrations on the formulated greases has been studied. The grease mixture is formulated using silicone oil as base oil, fumed silica and red gypsum as thickener, molybdenum disulphide as additive and iron octoate as anti-oxidant agent. Amount of fumed silica involves 2-20% wt (2% wt, 7% wt, 16% wt and 20% wt). All the fume silica proportions covered (70% gypsum, 30% FS), (60% gypsum, 40% FS) and (50% gypsum, 50% FS). The testing (penetration test, type of thickener, dropping point test, and amount of oil separated) have been done on the formulated greases to determine the properties. It was discovered that formulated grease has no dropping point until 260 o C which proves that the greases has stable structure at higher temperature. All the formulated greases proved to be composed of non-melt thickener type. As the amount of fumed silica and red gypsum increase oil separation decreases and the consistency of the greases increases. The penetration also significantly decreases as fumed silica addition increases. This is due to the larger strength and small size of fumed silica. The larger strength of fumed silica was thought to be due to the structure being knit together by means of primary valence bonds. It can be concluded that the formulated grease is multi purpose grease. Higher the amount of fumed silica and gypsum (thickener), better the grease’s quality. Therefore, the formulated greases has high potential to be used in wide range of industries such as the cars, ships, aircrafts and most of the industries that deals with heavy duty equipments.